2018
DOI: 10.1002/tqem.21603
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the additive structure of stand biomass equations in climatic gradients of Eurasia

Abstract: It has been established that in cold climatic zones any increase in rainfall leads to a corresponding decrease in biomass volume and in warm zones an increase in rainfall leads to an increase in biomass value. Furthermore, in water‐rich areas (900 millimeters [mm] per year), a rise in temperature causes an increase of biomass values, whereas in arid areas (300 mm per year) it causes reductions. These statements confirm previously recognized results that other researchers documented at both local and regional l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…There are more significant differences in our regularities for the dark-conifer genus Picea spp. when compared to the same Trans-Eurasian patterns obtained for the two-needled subgenus Pinus L. where the pine models manifested propeller-shaped surfaces (Usoltsev et al, 2018). If the decrease in the spruce stand biomass on the moisture-poor ecoregions (PRm = 300 mm) occurs less intensively compared to moisture-rich (PRm = 900 mm) ones as the transition from warm (Тm = +10°C) to cold (Tm = -30°C) zones, then the pine stand biomass in such moisture-poor ecoregions in the same temperature gradient significantly increases.…”
Section: Discussionmentioning
confidence: 65%
“…There are more significant differences in our regularities for the dark-conifer genus Picea spp. when compared to the same Trans-Eurasian patterns obtained for the two-needled subgenus Pinus L. where the pine models manifested propeller-shaped surfaces (Usoltsev et al, 2018). If the decrease in the spruce stand biomass on the moisture-poor ecoregions (PRm = 300 mm) occurs less intensively compared to moisture-rich (PRm = 900 mm) ones as the transition from warm (Тm = +10°C) to cold (Tm = -30°C) zones, then the pine stand biomass in such moisture-poor ecoregions in the same temperature gradient significantly increases.…”
Section: Discussionmentioning
confidence: 65%
“…Forests play a critical role in terrestrial ecosystems, covering a substantial portion of the terrestrial surface of the Earth. They are crucial in mitigating the human-induced greenhouse effect by absorbing carbon dioxide from the atmosphere [1][2][3]. Since forest biomass is a fundamental characteristic of forest ecosystems, its accurate estimation is essential for experts and policymakers interested in the exchange and storage of carbon on a global scale, nutrient cycling, and energy flow [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The application of these models had shown that climate has a significant impact on biomass and that these models produce more accurate predictions [17,18]. Usoltsev et al [19] showed that an increase in temperature of 1°C and an increase in precipitation of 100 mm would lead to an increase and decrease in the biomass of stands of Pinus sp. aged 100 years of 2.2% and 5.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%